2016
DOI: 10.4049/jimmunol.1500021
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Antimicrobial Peptide Cathelicidin for Controlling Helicobacter pylori Survival and Infection

Abstract: The antimicrobial peptide cathelicidin is critical for protection against different kinds of microbial infection. This study sought to elucidate the protective action of cathelicidin against Helicobacter pylori infection and its associated gastritis. Exogenous cathelicidin was found to inhibit H. pylori growth, destroy the bacteria biofilm, and induce morphological alterations in H. pylori membrane. Additionally, knockdown of endogenous cathelicidin in human gastric epithelial HFE-145 cells markedly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 61 publications
0
53
0
1
Order By: Relevance
“…The antimicrobial peptide cathelicidin has known activities against different microbial infections. Exogenous cathelicidin was recently found to inhibit H. pylori growth and disrupted bacterial biofilms . This study indicated that cathelicidin may function as natural antibiotic against H. pylori by reducing both the bacterial population and inflammation levels.…”
Section: Control Of H Pylori By the Innate Immune Systemmentioning
confidence: 87%
See 1 more Smart Citation
“…The antimicrobial peptide cathelicidin has known activities against different microbial infections. Exogenous cathelicidin was recently found to inhibit H. pylori growth and disrupted bacterial biofilms . This study indicated that cathelicidin may function as natural antibiotic against H. pylori by reducing both the bacterial population and inflammation levels.…”
Section: Control Of H Pylori By the Innate Immune Systemmentioning
confidence: 87%
“…This study indicated that cathelicidin may function as natural antibiotic against H. pylori by reducing both the bacterial population and inflammation levels. Interestingly, cathelicidin also strengthened the barrier function of gastric mucosa by stimulating mucus synthesis . Another proposed way to treat H. pylori infection is utilizing fatty acids, because various studies have shown their antibacterial effects .…”
Section: Control Of H Pylori By the Innate Immune Systemmentioning
confidence: 99%
“…It would be useful in future experiments to assess the functional impact of HVF and ECF with different concentrations of HDPs in terms of using bacterial killing assays. Moreover, there are published studies which demonstrate the antibacterial properties of both elafin and cathelicidn 42,43 .…”
Section: Authors Accepted Manuscript -24-sep-2017 Reproductionmentioning
confidence: 99%
“…More recently, cathelicidin has recently been shown inhibit H. pylori growth, destroy the bacteria biofilm, and induce morphological alterations in helicobacter pylori membrane 43 .…”
Section: Authors Accepted Manuscript -24-sep-2017 Reproductionmentioning
confidence: 99%
“…Multiple factors may be involved in the carcinogenesis of gastric cancer, including genetics and environmental factors. H. pylori is one of the most important environmental risk factors for gastric malignancies (13,14). Persistent inflammation in response to H. pylori infection is hypothesized to contribute to tumor cell proliferation and metastasis, and to affect survival (15,16).…”
Section: Introductionmentioning
confidence: 99%